2006
DOI: 10.1097/01.ico.0000164784.18290.45
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Pneumococcal Scleritis After Pterygium Excision

Abstract: Streptococcus pneumoniae must be considered as a possible agent in cases of necrotizing scleritis associated with pterygium excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…6,10,17,18 To our knowledge, there have been no previous reports with MRSA as a cause. MRSA has been recognized as a cause of nosocomial infections since the 1960s.…”
Section: Discussionmentioning
confidence: 75%
“…6,10,17,18 To our knowledge, there have been no previous reports with MRSA as a cause. MRSA has been recognized as a cause of nosocomial infections since the 1960s.…”
Section: Discussionmentioning
confidence: 75%
“…27,55,59, 148 Post-surgical and post-traumatic causes of scleritis are generally bacterial in nature, upwards of 45% of all cases. 32,58, 83,114,148 These exogenous infections may require combined medical and surgical management because of their more destructive and suppurative nature and poor antibiotic penetration. 22,59,154 Although a rare complication, pterygium excision is the most common surgical procedure associated with infectious scleritis, followed by scleral buckle surgery.…”
Section: Infectious Scleritismentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) was reported after pars plana vitrectomy [68], scleral buckling for retinal detachment [69], pterygium excision [70], after healing of a chronic diabetic foot ulcer due to same organism [6], and trauma [9 •• ]. Scleritis due to Streptococcus species is most commonly seen after pterygium surgery [2,19,45,71]. Ho et al have reported scleritis due to Streptococcus species (viridans group) after trauma [11 •• ].…”
Section: Microbiological Profilementioning
confidence: 99%